Pengaruh Promosi, Saluran Distribusi, Orang, Proses dan Bukti Fisik terhadap Keputusan Nasabah Menabung di Tabungan Simpeda pada PT. Kalbar Cabang Mempawah - Lastri , (JURNAL MANAJEMEN MOTIVASI, 2014)
This study aims to determine the effect of promotion, place, people, process and physical evidence against the decision of customers save money in the Savings Simpeda at PT. Bank Kalbar Cabang Mempawah. The shape of the research is a survey method. For the purposes of data collection, conducted interviews and questionnaire to a sample of 100 people, and using purposive sampling method specified purpose. From the results of hypothesis testing simultaneous effect (F test) showed that promotion, place, people, process and physical evidence simultaneously significantly influence consumer decisions to save. While the hypothesis test for promotion, it was found that partially have a significant influence on consumer decisions in Savings Simpeda save on PT. Bank Kalbar Cabang Mempawah